ALIGNING THE 1945 CONSTITUTION AND ISLAMIC PRINCIPLES FOR SOCIAL WELFARE IN INDONESIA - Muhammad Al Mighwar; Evi Sopiah (UIN Sunan Gunung Djati Bandung, 2024)
Indonesia, a Muslim-majority country, strives to optimize its social welfare programs. While the 1945 Constitution guarantees social rights and Islamic principles provide guidance, there is a gap in exploring how these can be better aligned. This research aims to explore how social rights in the 1945 Constitution (Chapter XIV) can be aligned with the Dharuriyat al-Khams (five essential human needs) by Shatibi to strengthen social welfare programs. The research employed a qualitative approach using a literature study and thematic analysis method by Miles and Huberman, encompassing data collection, data reduction, data display, and conclusion/ verification of primary and secondary data. The research findings demonstrate that the 1945 Constitution, particularly Chapter XIV, guarantees social welfare rights and obligates the government to fulfill them, the Dharuriyat al-Khams, introduced by Imam Shatibi, is part of the maqashid shariah (objectives of Islamic law) that aims to achieve social welfare by fulfilling five basic human needs, substantively, these two concepts synergize and can be effectively integrated to strengthen social welfare programs in Indonesia. This research enriches the discourse on Islamic economics in strengthening programs and addressing social welfare issues, particularly concerning essential human rights in Muslim-majority countries.